Christian realism and the revival of public theology - McDaniel, Charles, Jr., 1958- (Routledge studies in religion and politics., 2026)
Christian Realism and the Revival of Public Theology analyzes Reinhold Niebuhr's The Children of Light and the Children of Darkness 80 years after publication and argues that it provides pertinent lessons for the contemporary era. This book considers how Niebuhr's book-as well as his other work-remains relevant and retains insights for an America which seems increasingly to be losing its moral bearings and political courage. The author examines the roots of political polarization in Niebuhr's categories of the children of light and the children of darkness, finding it a more useful binary than liberalism vs. conservatism for understanding America's culture wars and the growing sense that its political institutions are in terminal decay. This book seeks to show how public theology offers resources to foster democratic and moral renewal. It concludes by calling for a reinvigorated civil religion to promote unity rather than division. This book will appeal to scholars of American politics, Christian ethics, Christian Realism, public theology, and American religious history as well as historians of American Christianity.